1991
DOI: 10.1128/iai.59.10.3801-3810.1991
|View full text |Cite
|
Sign up to set email alerts
|

Roles of human peripheral blood leukocyte protein kinase C and G proteins in inflammatory mediator release by isogenic Escherichia coli strains

Abstract: The signal transduction pathway (protein kinase C [PKC], calcium influx, and G protein involvement) was studied with isogenic Escherichia coli strains expressing different types of adhesins (MSH+/- MS-Fim+/-, P-MRH+/- P-Fim+/-, and S-MRH+/- S-Fim+/-) or varying only in the expression of E. coli alpha-hemolysin. As target cells, human polymorphonuclear granulocytes (PMN) and a lymphocyte-monocyte-basophil (LMB) cell suspension were used. The alpha-hemolysin-producing (Hly+) strain E. coli K-12(pANN5211) induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The difference in binding levels between HlyA and LktA or EhxA also argues in favor of a specific interaction for HlyA. Existence of a receptor per se for HlyA is supported by several studies demonstrating cell signalling events triggered by sublytic doses of HlyA on leukocytes (11,12,17). Interestingly, greater specificity in the requirements of HlyA structural domains would be expected than were discernable in these assays if HlyA binds in a specific manner.…”
Section: Discussionmentioning
confidence: 82%
“…The difference in binding levels between HlyA and LktA or EhxA also argues in favor of a specific interaction for HlyA. Existence of a receptor per se for HlyA is supported by several studies demonstrating cell signalling events triggered by sublytic doses of HlyA on leukocytes (11,12,17). Interestingly, greater specificity in the requirements of HlyA structural domains would be expected than were discernable in these assays if HlyA binds in a specific manner.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the pore formation leading to calcium influx was thought to be the active principle for inflammatory mediator release from human target cells. Previously, we have shown that the E. coli alpha-hemolysin leads to inflammatory mediator release from human leukocytes and platelets via a distinct signal transduction cascade including G proteins, calcium influx, and protein kinase C activation (23,28). Furthermore, it is established that the hydrolysis of the membrane inositol phospholipids represents one major step in the cellular signalling process by the E. coli alpha-hemolysin (18,24,32).…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysin-producing (Hly+) Escherichia coli strains are isolated from patients with extraintestinal infections such as urinary tract infections, bacteremia, and septicemia (15). The pathogenic relevance of the alpha-hemolysin has been proven in several animal as well as in vitro models (3,21,23). After interaction with soluble hemolysin or with hemolysin-producing E. coli bacteria, human neutrophils produce reactive oxygen species, generate the chemotactically active leukotriene B4 (LTB4) and release cytoplasmic and lysosomal enzymes, e.g., P-glucuronidase and lysozyme; human basophils release histamine (23).…”
mentioning
confidence: 99%
“…In contrast, E. coli alpha-hemolysin inhibits cytokine (interleukin 6 , tumor necrosis-factor alpha [TNF-cx], and IL-11) release from human monocytes (22). The cellular responses to E. coli alpha-hemolysin are mediated by a complex signal transduction cascade which is dependent on the cell type (21). In this regard, substantial evidence for the fact that protein kinase C and guanine nucleotide-binding proteins (G proteins) play an essential role in the cellular activation process leading to reactive oxygen metabolites and mediators of inflammation such as leukotrienes from human neutrophils was obtained (21,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation